Rhododendron yuanbaoshanense (Ericaceae), a new species from Guangxi, China - Deng, Yi-Hui; Pan, Bo; Ding, Tao; Liu, Hong; Qin, Xue-Lian; Huang, Zi-Xiong; Deng, Min-Min (Phytotaxa, 2025)
A new species of Rhododendron (Ericaceae) in subgen. Hymenanthes, sect. Ponticum, subsect. Fortunea from Yuanbaoshan, northern Guangxi, China, namely R. yuanbaoshanense, is described and illustrated. The new species is most similar to R. yuefengense and R. orbiculare, but it differs from R. yuefengense by its broader ovate to orbicular leaf blades with a cordate-auriculate base, cylindric petioles, and longer inflorescence rachis. It is distinguished from R. orbiculare in having 8–17-flowered inflorescences with longer rachis, funnelform-campanulate to campanulate corollas that are pink to pale pinkish-purple and sparsely glandular outside, and densely white glandular style.